2012
DOI: 10.1016/j.marpolbul.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of dredging and other sediment disturbances on corals: A review

Abstract: A review of published literature on the sensitivity of corals to turbidity and sedimentation is presented, with an emphasis on the effects of dredging. The risks and severity of impact from dredging (and other sediment disturbances) on corals are primarily related to the intensity, duration and frequency of exposure to increased turbidity and sedimentation. The sensitivity of a coral reef to dredging impacts and its ability to recover depend on the antecedent ecological conditions of the reef, its resilience a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
483
0
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 657 publications
(508 citation statements)
references
References 210 publications
(274 reference statements)
6
483
0
19
Order By: Relevance
“…High fluxes of both terrigenous and autochthonous sediments are widely identified to have both direct and indirect inhibitory effects on coral reef growth (Larcombe et al, 2001;Erftemeijer et al, 2012;Sanders and Baron-Szabo, 2005;Salles et al, 2018a). For instance, elevated turbidity on midouter platform reefs caused by the suspension of sediment on the Pleistocene reef substrate during initial flooding ∌ 9 ka is hypothesised to be responsible for a delayed initiation of coral growth in the southern Great Barrier Reef (GBR) (Dechnik et al, 2015;Salles et al, 2018b).…”
Section: Sediment Inputmentioning
confidence: 99%
See 2 more Smart Citations
“…High fluxes of both terrigenous and autochthonous sediments are widely identified to have both direct and indirect inhibitory effects on coral reef growth (Larcombe et al, 2001;Erftemeijer et al, 2012;Sanders and Baron-Szabo, 2005;Salles et al, 2018a). For instance, elevated turbidity on midouter platform reefs caused by the suspension of sediment on the Pleistocene reef substrate during initial flooding ∌ 9 ka is hypothesised to be responsible for a delayed initiation of coral growth in the southern Great Barrier Reef (GBR) (Dechnik et al, 2015;Salles et al, 2018b).…”
Section: Sediment Inputmentioning
confidence: 99%
“…Decades of experimentation carried out on the sensitivity of particular species to sediment have informed a generic understanding of the threshold levels of corals to the effect of natural sedimentation (Hubbard, 1986;Rogers, 1983;Stafford-Smith, 1993); however, these thresholds have only been partially quantified in the literature, and tolerance at the assemblage level is difficult to constrain due to site and within-species variations (Erftemeijer et al, 2012). It has been shown that even under uniform sediment input regimes, inter and intra-site variations in sedimentationresuspension regimes occur depending on water depth and exposure to wave energy (Wolanski et al, 2005).…”
Section: Sediment Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Dredging is an extreme event causing high sedimentation and is associated with construction of hotels, runways, roads, harbors, and military installations, as well as with beach replenishment [17,18]. It has been considered as a high-risk event because of its likely deleterious effects to the marine environment and is one of the biggest potential sources of reef degradation resulting from human activities, being an especially severe risk in developing countries [17,19].…”
mentioning
confidence: 99%
“…Live coral cover decreased by 40% and partial coral death significantly increased during a dredging operation in Hong Kong [23]. Although the detrimental effects of dredging on coral reefs have been reviewed [17,18,22,24], the impact of dredging on corals and coral reef ecosystems is complex and far from fully understood [18]. Few studies have presented detailed and quantitative data on coral community changes before and after a dredging event [22].…”
mentioning
confidence: 99%